2017
DOI: 10.1080/09637486.2017.1373079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrates on the in vitro kinetics of steviol glucuronidation and interaction between steviol glycosides metabolites and UGT2B7

Abstract: Steviol glycosides, a natural sweetener, may perform bioactivities via steviol, their main metabolite in human digestion. The metabolising kinetics, i.e. glucuronidation kinetics and interaction between steviol glycosides or their metabolites and metabolising enzyme, are important for understanding the bioactivity and cytotoxicity. The present study investigated kinetics of steviol glucuronidation in human liver microsome and a recombinant human UDP-glucuronosyltransferases isomer, UGT2B7, along with molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Natural toxins can be produced through the accumulation of some chemical substances and elements that the animal gets from food [1], they come as residues from dilapidated cells or some vital processes in the body, causing sheep inside the body that acts as a substance that cannot be used in the metabolic processes and difficult to get rid of [2]. [3] indicated that the animal is able to get rid of these substances accumulated inside the body that are difficult to get rid of in the usual ways through a mechanism called Glucuronide, known as Glucuronoside [4]. Glucuronic acid binds with accumulated substances by means of a glycosidic bond and ultimately these bound substances are excreted, which have a higher solubility than the accumulated substances out of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Natural toxins can be produced through the accumulation of some chemical substances and elements that the animal gets from food [1], they come as residues from dilapidated cells or some vital processes in the body, causing sheep inside the body that acts as a substance that cannot be used in the metabolic processes and difficult to get rid of [2]. [3] indicated that the animal is able to get rid of these substances accumulated inside the body that are difficult to get rid of in the usual ways through a mechanism called Glucuronide, known as Glucuronoside [4]. Glucuronic acid binds with accumulated substances by means of a glycosidic bond and ultimately these bound substances are excreted, which have a higher solubility than the accumulated substances out of the body.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of foods and supplements with the lipid bilayer and mitochondrial health regulatory effects to reduce the risk of disease have been reported, including flavone O-glycosides and flavone C-glycosides components [56]. Currently, there are studies that have confirmed the interaction between O-glycosides and UGT2B7 [57], but we have not found any report on the interaction between C-glycosides and UGT2B7. How-ever, the sites and applicability of these components in cell metabolism have not been well clarified.…”
Section: Discussionmentioning
confidence: 57%
“…Nutrients 2023, 15, x FOR PEER REVIEW 12 of 16 [57], but we have not found any report on the interaction between C-glycosides and UGT2B7. However, the sites and applicability of these components in cell metabolism have not been well clarified.…”
Section: Discussionmentioning
confidence: 61%
“…Steviol was mainly surrounded by the active amino acids of ligand-UGT2B7, including Arg352, Leu347, Lys343, Phe339, Tyr354, Lys355, and Leu353. 85 These studies revealed the kinetic characteristics of enzymes as well as the optimum reaction conditions that could facilitate the in vitro synthesis of steviol glycoside and its mass production.…”
Section: Microbial Synthesis Of Steviol Glycosides and The Precursorsmentioning
confidence: 99%